2002
DOI: 10.1053/jhep.2002.34851
|View full text |Cite
|
Sign up to set email alerts
|

Underexpression of mRNA in human hepatocellular carcinoma focusing on eight loci

Abstract: Genetic alterations associated with human hepatocellular carcinoma (HCC) have been reported previously, but are not sufficient to specify differences of HCCs from precancerous diseases of the liver, such as hepatitis, hepatic fibrosis, and cirrhosis. In the present study, we performed differential gene display analysis (DGDA) to clarify the specific genetic alterations associated with gene expression changes in the course of development of HCC from chronic viral hepatitis. Four pairs of surgically resected HCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 30 publications
10
62
1
Order By: Relevance
“…34,35 A recent study has shown that CPS1 gene transcription is downregulated in liver cancer tissues. 36 However, the absence of CPS1 in the cancer cell lines cannot be explained entirely by the hepatocellular differentiation state. It is known that all three cell lines express abundant levels of albumin and a-1 antitrypsin, indicating that many liver-specific transcription factors are present in these cell lines.…”
Section: Identification Of Hepmentioning
confidence: 97%
“…34,35 A recent study has shown that CPS1 gene transcription is downregulated in liver cancer tissues. 36 However, the absence of CPS1 in the cancer cell lines cannot be explained entirely by the hepatocellular differentiation state. It is known that all three cell lines express abundant levels of albumin and a-1 antitrypsin, indicating that many liver-specific transcription factors are present in these cell lines.…”
Section: Identification Of Hepmentioning
confidence: 97%
“…Several groups have independently suggested that CYP2E1 mRNA is down regulated in tumor tissues 26 and is differentially expressed in different liver tissues. 27 To our knowledge, our study is the first combined study to investigate the expression of CYP2E1 at both mRNA and protein levels in relation to HCC.…”
Section: Cyp2e1 Protein Expression and Clinicopathological Features Omentioning
confidence: 99%
“…OATP1B1 has been reported to be down-regulated during neoplastic transformation in the liver (Kinoshita and Miyata, 2002). It was also shown that OATP1B1 and OATP1B3 are not detectable in HepG2 cells, widely used as a model of human hepatic carcinoma (Cui et al, 2003).…”
mentioning
confidence: 99%